EKSISTENSI PANDEMI COVID-19 DALAM STUDI MASALAH SOCIAL DI INDONESIA - Syamsuni HR; Rismawati; Sumarni; Elli Elli (Jurnal Sosial Humaniora, 2022)
The level of public understanding of existence of Covid-19 in Indonesia is a challenge in implementing the Covid-19 pandemic confectionery program and creating social phenomena that often occur in the midst of Covid-19 pandemic. This study aims to provide an overview of the existence of Covid-19 in the perspective of social phenomenology by using the phenomenological analysis research method, the nature of the study conducted is descriptive analysis of data sourced from the community and health workers. This study uses a qualitative method with a literature and empirical approach. The existence of the Covid-19 pandemic has resulted in phenomena in society including the handling of corpses exposed to Covid-19, public distrust of Covid-19, the incompatibility of the rules for handling the Covid-19 pandemic with applicable legal rules and many people refusing to be vaccinated.